Law enforcement with rent dissipation - Murat C. Mungan; J. Shahar Dillbary (Public Choice, 2026)
Abstract We consider a framework which brings together losses arising from rent-dissipation and the workhorse model of law enforcement. Governmental actors engage in a contest to share the proceeds from the enforcement of the law through monetary fines, which leads to rent-dissipation. This causes monetary sanctions to be costly, rendering the model used for studying nonmonetary sanctions a better fit for their analysis. The effect of rent-dissipation on optimal sanctions is directly related to the sanction elasticity of offenses measured at the classic optimum (i.e., where the expected sanction equals the direct harm from the offense). When offenses are inelastic, the optimal sanction is smaller than the classic optimum and it is decreasing in the degree of rent-dissipation; and a legislator who does not fully internalize contest costs chooses an overly punitive sanction which is smaller than the classic optimum. The opposite results are obtained when offenses are elastic. We discuss implications and extensions.